Recommendations for the use of long-term central venous catheter (CVC) in children with hemato-oncological disorders: management of CVC-related occlusion and CVC-related thrombosis. On behalf of the coagulation defects working group and the supportive the - Giordano, Paola; Saracco, Paola; Grassi, Massimo; Luciani, Matteo; Banov, Laura; Carraro, Francesca; Crocoli, Alessandro; Cesaro, Simone; Zanazzo, Giulio Andrea; Molinari, Angelo Claudio (Ann Hematol, 2015)
Central venous catheters (CVC), used for the management of children with hemato-oncological disorders, are burdened by a significant incidence of mechanical, infective, or thrombotic complications. These complications favor an increasing risk in prolongation of hospitalization, extra costs of care, and sometimes severe life-threatening events. No guidelines for the management of CVC-related occlusion and CVC-related thrombosis are available for children. To this aim, members of the coagulation defects working group and the supportive therapy working group of the Italian Association of Pediatric Hematology and Oncology (AIEOP) reviewed the pediatric and adult literature to propose the first recommendations for the management of CVC-related occlusion and CVC-related thrombosis in children with hemato-oncological disorders.
Keywords: Adult; Blood Coagulation Disorders; Catheter Obstruction; Catheterization, Central Venous; Central Venous Catheters; Child; Hematologic Neoplasms; Humans; Risk Factors; Thrombosis